Uncovering the Structure Evolution of ZnCo Heptaclusters for Electrochemical Behavior Transformation via the Total Reduction Strategy - Shi, Yu‐Xin; Xie, Xiang‐Ting; Li, Jia‐Ning; Yang, Shao‐Xi; Wang, Zheng; Li, Yuebin; Peng, Xu (Advanced functional materials, 2025)
In the realm of energy conversion and storage devices, transition metal porous oxide composites have been the subject of extensive research and interest. Supercapacitors and electrocatalysis, as two important energy conversion and storage modalities, exhibit a competitive yet balanced relationship, much like a state of equilibrium. In this work, a comprehensive reduction approach is employed during the pyrolysis of anionic/cationic doped molecular clusters, specifically [Zn7L6(μ3‐OCH3)6]·[CoCl4] (where L = 2‐methoxy‐6‐((methylimino)‐methyl)phenolate, abbreviated as Zn7Co1). Notably, within an inert atmosphere, a significant quantity and diverse range of reducing gases are generated throughout the entire pyrolysis temperature spectrum of Zn7Co1, as monitored by thermogravimetry‐mass spectrometry (TG‐MS). It is observed that the production of these reducing gases led to a reduction in the valence state of metal oxides, thereby inducing a shift in the electrochemical behavior from oxygen evolution to supercapacitive performance at different pyrolysis temperatures. The Zn7Co1‐350 sample demonstrated oxygen evolution reaction (OER) performance, with an overpotential of 168 mV at a current density of 10 mA·cm−2. Conversely, the Zn7Co1‐700 sample exhibited excellent capacitance performance, attaining a capacitance of 1406 F·g−1 at a current density of 1 A·g−1. The research findings offer a novel synthesis of molecular clusters with electrical performance conversion capabilities via a total reduction strategy. In this work, Zn7Co1 cluster is pyrolyzed via a total reduction strategy. Reducing gases generated during pyrolysis induced both structural transformation and valence change, shifting electrochemical behavior from OER to supercapacitive. The Zn7Co1‐350 sample demonstrated OER performance, with an overpotential of 168 mV at 10 mA·cm−2, while the Zn7Co1‐700 sample exhibited a capacitance of 1406 F·g−1 at 1 A·g−1.